Development Prospect of Nepal - Shah, Anil Keshary (Socio-Economic Development Panorama, 2009)
This is a unique effort entrusted to dwell on economic transformation through the lessons to be carried out to gain a double digital growth. It succinctly presents a unique thought behaviour advocating steps to carve out good neighbourly attitudes and rapprochement economic activities to accelerate the pace of development. Initiation of hydropower or alternative source of energy, adherence towards a more practical investment economic building climate following Build Own Operate and Transfer (BOOT) system, venture capital or embracing an enterprising more practical feasible economic climate is a harbinger that Nepal needs to jumpstart into so as to accelerate the pace of development. Similarly, it highlights strategic ways to work along to accelerate the pace ahead to build a sustainable health, education forest resources mines, minerals, and agriculture sector system in an enterprising, democratic and integrative manner. Key words: India and China, economic transformation, energy resources, economic potential, tourism, education, health, forest, mines, agriculture Socio Economic Development Panorama; Vol. 1; No. 4, 2009; January-June